Aplicação da tecnologia LoRa em enlaces de comunicação óptica por luz visível - Gadens, Rafael Nerone (2021)
This work presents a study about the use of LoRa (Long Range) radio frequency technology for data communication using visible light, texti Visible Light Communications (VLC). The LoRa technique was implemented via software in a wireless optical communication system, considering the non-linearities of the LED emitter and, through simulations in a wireless channel with a line of sight, in outdoor and indoor environments, the performance of the proposed system in terms of communication link range and bit error rate (BER). As a reference, the performance of the proposed LoRa technique is compared with the BPSK applied in the same VLC system. For all scenarios considered, LoRa, in configurations similar to those found in commercial chipsets, shows superior performance, reaching 34 m in a clean outdoor environment and 16 m for an environment with moderate fog, using spread factor 7, optical output power of 2.6 W in the transmitter and as receiver, a photodiode with 1502 of area and responsiveness of 0.17 A/W. It also discusses the impact of the main parameters of the system, allowing them to be optimized, improving the communication range of the proposed system.